2015
DOI: 10.1103/physreva.92.042702
|View full text |Cite|
|
Sign up to set email alerts
|

Polarization measurement of dielectronic recombination transitions in highly charged krypton ions

Abstract: We report linear polarization measurements of x rays emitted due to dielectronic recombination into highly charged krypton ions. The ions in the He-like through O-like charge states were populated in an electron beam ion trap with the electron beam energy adjusted to recombination resonances in order to produce K α x rays. The x rays were detected with a newly developed Compton polarimeter using a beryllium scattering target and 12 silicon x-ray detector diodes sampling the azimuthal distribution of the scatte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 72 publications
(109 reference statements)
0
33
0
Order By: Relevance
“…10. Recently, photon emission asymmetries were measured with high accuracy for radiative electron recombination with few-electron Fe ions [15]. The presented calculation shows the large sensibility of the photon emission asymmetry to the Breit interaction.…”
Section: Methods Of Calculationmentioning
confidence: 96%
See 1 more Smart Citation
“…10. Recently, photon emission asymmetries were measured with high accuracy for radiative electron recombination with few-electron Fe ions [15]. The presented calculation shows the large sensibility of the photon emission asymmetry to the Breit interaction.…”
Section: Methods Of Calculationmentioning
confidence: 96%
“…The recent studies revealed that the Breit interaction may give an "laywer92@mail.ru important and even dominant contribution to the cross section of the dielectronic recombination with few-electron highly charged ions [5,[11][12][13][14][15],…”
Section: Introductionmentioning
confidence: 99%
“…Thus, X‐ray radiation from the intershell resonant recombination process is anisotropic and polarized . For an electric dipole (E1) transition, the degree of linear polarization of X‐ray emission can be expressed as follows: P=3A2α2df2A2α2df, where A 2 is the alignment parameter used to describe the nonstatistical magnetic sublevel population of the intermediate resonance state. Following the density matrix theory, for the resonant capture of an unpolarized electron, the alignment parameter can be expressed as follows: A2=Mfalse(1false)Jd+M5false(2Jd+1false)()center center centerarrayJdarrayJdarray2arrayMarrayMarray0σM, where M is the magnetic quantum number, the quantity in large parentheses represents the Wigner 3‐ j symbol, σ M is the resonant capture cross sections from the initial state to the magnetic sublevels of the intermediate excited state, normalized such that MσM=1.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Following the density matrix theory, for the resonant capture of an unpolarized electron, the alignment parameter can be expressed as follows: A2=Mfalse(1false)Jd+M5false(2Jd+1false)()center center centerarrayJdarrayJdarray2arrayMarrayMarray0σM, where M is the magnetic quantum number, the quantity in large parentheses represents the Wigner 3‐ j symbol, σ M is the resonant capture cross sections from the initial state to the magnetic sublevels of the intermediate excited state, normalized such that MσM=1. α2df in Equation is an intrinsic anisotropy parameter that is completely determined by the total angular momentum of the intermediate excited state J d and the final state J f and can be expressed as follows: α2df=false(1false)1+Jd+Jf3false(2Jd+1false)2×{}center center centerarray1array1array2arrayJdarrayJdarrayJf, where the quantity in the large parentheses denotes the wigner 6‐ j symbol.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Since the resonant excitation in DR is solely evoked by the interaction of the active electrons, the experimental determination of cross sections provides one new insights into relativistic electron interactions in a dynamical process. Recently, the experiments became sensitive to the contribution of the generalized Breit interaction [23,36] to DR resonance strengths, as well as to the linear polarization of x rays emitted during DR [37,38]. Also, the theoretical description of the process requires non-trivial additions to the many-body theory of atomic structures.…”
Section: Introductionmentioning
confidence: 99%